2018
DOI: 10.14748/vmf.v7i1.5074
|View full text |Cite
|
Sign up to set email alerts
|

Application of aesthetic crowns in children patients

Abstract: Неснемаемото коронково протезиране се приема за сигурен и успешен метод за възстановяване увредените млечни и постоянни зъби. Цел на изследването е да се проучи приложението на естетичните корони в ежедневната практика на лекарите по дентална медицина в България. Източник на информация беше специално разработена за целта анкетна карта. Обект на изследване са 767 лекари по дентална медицина от цялата страна. Резултатите са обработени статистически, като са използвани методите на вариационен, сравнителен и корел… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has been concluded that traumas are not basic indication for endodontic treatment. Traumas are most often related to single clinical cases of emergency [7] and treatment [13] in children with primary dentition. According to other researchers the most frequent established clinical finding related to the need of endodontic therapy is pulp necrotic alteration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been concluded that traumas are not basic indication for endodontic treatment. Traumas are most often related to single clinical cases of emergency [7] and treatment [13] in children with primary dentition. According to other researchers the most frequent established clinical finding related to the need of endodontic therapy is pulp necrotic alteration.…”
Section: Discussionmentioning
confidence: 99%